EFEKTIFITAS PISTIA STRATIOTES L. DAN ECHINODORUS PALAEFOLIUS DALAM PENYERAPAN FERRUM (FE) DALAM AIR SUMUR MENGGUNAKAN METODE FITOREMEDIASI - Citra Mawar Pratiwi; Ferry Kriswandana; Iva Rustanti Eri Wardoyo (Poltekkes Kemenkes Surabaya, 2022)
Clean water is a basic need for living things, one source of clean water is groundwater. The problem that is often encountered in groundwater from dug wells is the content of heavy metal Fe. The purpose of this study was to determine the effectiveness of the absorption of heavy metal iron (Fe) in well water with Pistia stratiotes L. and Echinodorus palaefolius for 14 days using a phytoremediation process. This type of research is an experimental design using a pretest-posttest model with a control group that compares the occurrence of differences in the decrease in iron (Fe) levels of 9.86 mg/l in well water by collecting data by examining the results of iron (Fe) levels in well water. before and after treatment. Analysis of the data using the Independent T-test. The results of the study showed a decrease in iron (Fe) levels in well water after the phytoremediation process for 14 days. In Pistia stratiotes L. the level of iron (Fe) in well water was 0.67 mg/l and Echinodorus palaefolius was 0.58 mg/l. The effectiveness of Pistia stratiotes L. was 92.85% and Echinodorus palaefolius was 93.81% in reducing iron (Fe) levels in well water. Phytoremediation using Pistia stratiotes L. and Echinodorus palaefolius is effective in reducing iron (Fe) levels according to Permenkes No. 32 of 2017. The phytoremediation process using Pistia stratiotes L. and Echinodorus palaefolius can be recommended to reduce iron (Fe) levels in well water so that it meets quality standards.